The Effect of Maternal Stress Activation on the Offspring during Lactation in Light of Vasopressin - Anna Fodor; Dóra Zelena (The Scientific World Journal, 2014)
Although it is obvious that preconceptional effects as well as stressors during pregnancy profoundly influence the progeny, the lactation period seems to be at least as important. Here we summarize how maternal stressors during the lactation period affect the offspring. As vasopressin is one of the crucial components both for stress adaptation and social behavior, special emphasis was given to this neuropeptide. We can conclude that stressing the mother does not have the same acute effect on the hypothalamo-pituitary-adrenocortical axis (as the main target of stress adaptation) of the pups as stressing the pups, but later endocrine and behavioral consequences can be similar. Vasopressin plays a role in acute and later consequences of perinatal stressor applied either to the mother or to the offspring, thereby contributing to transmitting the mothers’ stress to the progeny. This mother-infant interaction does not necessarily mean a direct transmission of molecules, but rather is the result of programming the brain development through changes in maternal behavior. Thus, there is a time lag between maternal stress and stress-related changes in the offspring. The interactions are bidirectional as not only stress in the dam but also stress in the progeny has an effect on nursing.